Analisis Penerapan Pengisian Jabatan Aparatur Sipil Negara (ASN) Tertentu Dari Kalangan Non Pegawai Negeri Sipil (PNS) : (Suatu Kajian Terhadap Peraturan Pemerintah Nomor 49 Tahun 2018 tentang Manajemen PPPK) - Subagja, Aba; Rifai, Anis; Fuad, Fokky (Jurnal Bedah Hukum, 2024)
In Law Number 5 of 2014 concerning State Civil Apparatus (UU ASN) there are provisions regarding the position of employees outside the Civil Servants (PNS) or non-PNS employees, namely Government Employees with Employment Agreements (PPPK). Regarding personnel management for PPPK, the government further regulates through Government Regulation Number 49 of 2018 concerning PPPK Management (PP 49/2018) in order to produce PPPK that is professional, has basic values, professional ethics, free from political intervention, clean from corrupt practices, collusion and nepotism. The issuance of Presidential Regulation Number 38 of 2020 concerning Types of Positions That Can Be Filled by Government Employees with Employment Agreements (Perpres 38/2020) limits the types of positions and criteria for positions that can be filled by non-PNS or PPPK employees, thereby minimizing the potential for discrimination and social jealousy between ASN employees. The problems that will be discussed in this study are related to what types of positions can be filled by ASN non-PNS or PPPK employees and how the practice of implementing procedures for filling positions from PPPK circles. In this study the authors used the normative-empirical method, examining the implementation of positive legal provisions and written documents in each particular legal event that occurred. The results of this study are that there are certain ASN positions that can be filled by PPPK, namely Functional Positions, High Leadership Positions and Other Positions whose criteria are regulated in Presidential Regulation 38/2020, besides that the implementation of filling high leadership positions that can be filled by PPPK in practice has not fully based on the criteria regulated by the provisions of laws and regulations.